1963
DOI: 10.1136/bmj.1.5329.538-c
|View full text |Cite
|
Sign up to set email alerts
|

Methyldopa and Depression

Abstract: BDICAL JHURNAL _~~~~~~~~~~~~~~~~~~~EIA of patients requiring these should be few, and as long as penicillin is effective should be preferred to the use of other antibiotics.-I am, etc.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1966
1966
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Sourkes (1) first reported its basic ability to inhibit the decarboxylation of dopa in an in vitro system. In animal studies, it has been found to decrease the CNS concentration of serotonine (2), dopamine, and norepinephrine (3,4) and, in clinical practice, to induce sedation (5-7), depression (8)(9)(10) and toxic psychosis (11,12). The first clinical trials did not establish its efficacy in the treatment of schizophrenia (13)(14)(15)(16)(17), periodic catatonia (18) or mania (19).…”
mentioning
confidence: 99%
“…Sourkes (1) first reported its basic ability to inhibit the decarboxylation of dopa in an in vitro system. In animal studies, it has been found to decrease the CNS concentration of serotonine (2), dopamine, and norepinephrine (3,4) and, in clinical practice, to induce sedation (5-7), depression (8)(9)(10) and toxic psychosis (11,12). The first clinical trials did not establish its efficacy in the treatment of schizophrenia (13)(14)(15)(16)(17), periodic catatonia (18) or mania (19).…”
mentioning
confidence: 99%
“… 6 , 27 However, some studies have not shown any differences in adverse events, when comparing fluoxetine with other drugs, 28 - 30 ; (6) methyldopa, which presents bradycardia and depression in the elderly, with level of evidence = 5. 6 , 31 , 32 However, some studies showed no differences in adverse events, when comparing methyldopa with other drugs; 33 , 34 (7) nifedipine presents hypotension and constipation, with level of evidence = 2; 6 , 35 - 37 (8) thioridazine is a typical neuroleptic with great potential for extrapyramidal and central nervous system symptoms, with level of evidence = 5; 6 , 38 (9) promethazine has anticholinergic effects, with level of evidence = 3; 38 , 39 and (10) ferrous sulfate, which at doses greater than 325 mg/day may increase constipation, with level of evidence = 5. 6 …”
Section: Discussionmentioning
confidence: 99%
“…6,27 However, some studies have not shown any differences in adverse events, when comparing fluoxetine with other drugs, [28][29][30] ; (6) methyldopa, which presents bradycardia and depression in the elderly, with level of evidence = 5. 6,31,32 However, some studies showed no differences in adverse events, when comparing methyldopa with other drugs; 33,34 (7) nifedipine presents hypotension and constipation, with level of evidence = 2;…”
mentioning
confidence: 99%
“…Insomnia, nightmares and hallucinations may also occur with depression occasionally (72,75). The combination of methyldopa with other drugs can cause neuropsychiatrie problems: hallucinations with pargyline (81); nightmares or depression with Rauwolfia (82); agitation with amitriptyline (83), and puerperal depression and hallucination with phenothiazines (84). In general, the onset of methyldopa-induced depression seems easier to recognize than reserpine-induced depression, probably because the former has a more readily identifiable symptom such as tiredness.…”
Section: Methyldopamentioning
confidence: 99%